Amorphous and crystalline thioacetamide ice: Infrared spectra as a probe for temperature and structure - Góbi, Sándor (2020)
In this work we report the effect of intermolecular interactions on the structure of thioacetamide (CH3CSNH2) as a function of temperature, monitored by IR spectroscopy. Thin films of amorphous thioacetamide ice were deposited at 10 K and gradually warmed up to 260 K. Irreversible spectral changes between 180 and 200 K provide evidence for crystallization of the ice. Quantum chemical computations on a dodecamer of thioacetamide aided the assignment of the IR spectrum of the amorphous ice for the first time and allowed reassessing some of the earlier vibrational assignments of the crystalline form. This provides fundamental knowledge regarding the structure determination of thioacetamide (amorphous or crystalline). Upon repeated cooling and annealing of the crystalline sample, reversible spectral changes could also be detected, indicating that at temperatures below 150 K the methyl group undergoes a hindered torsional motion, while at higher temperatures the vibrationally excited methyl group exhibits virtually barrierless torsion. This interpretation was supported by computations, which have also provided estimates for the mean H-bond energies in the crystal. Investigation of low-temperature thioacetamide ice might be of interest from the astrophysical point of view. Moreover, the reversible temperature dependence of the vibrational spectra for the compounds with internal methyl rotor, such as thioacetamide, could serve as a molecular thermometer for cryogenic crystals.